A systemic model for implementing land value capture to support urban rail transit infrastructure projects. (February 2022) - Li, Xinjian; Love, Peter E.D.; Luo, Hanbin; Fang, Weili
Abstract: Urban rail transit (URT) infrastructure is critical for the economic and social development of an economy. The construction and operation of URT systems invariably require significant investment. Yet, governments are often subjected to fiscal constraints and cannot provide taxpayers with efficient and effective rails services. Development-based land value capture (LVC), a method for funding and financing infrastructure, can support URT delivery. However, there has been a tendency to apply LVC in a piecemeal manner. Thus, an absence of a systemic strategy to assist policy-makers with the implementation of LVC contributes to the ongoing debate about its effective use to support URT. Using the lens of systems thinking, our research aims to address the following research question: How can governments create an effective LVC strategy to support the procurement of their URT systems and networks? Drawing on the experiences of three Chinese cities, we develop a systemic model that policy-makers can draw upon to ensure the successful implementation of LVC. The contributions of our paper are threefold as we: (1) summarise the threads of LVC knowledge and its associated challenges; (2) provide the state-of-art experience of three cities that are using LVC to support their URT projects; and (3) identify the underlying systemic interdependencies that influence the successful adoption of the LVC strategy to support the URT system and network.